Optoelectronic Properties of MoS2 in Proximity to Carrier Selective Metal Oxides. Issue 9 (8th March 2022) - Lattyak, Colleen; Vehse, Martin; Gonzalez, Marco A.; Pareek, Devendra; Gütay, Levent; Schäfer, Sascha; Agert, Carsten
Abstract: Transition metal dichalcogenides are an exciting class of new absorber materials for photovoltaic applications due to their unique optoelectronic properties in the single to few‐layer regime. In recent years, these materials have been intensively studied, often utilizing conventional substrates such as sapphire and silicon dioxide on silicon. This study investigates the optical properties of molybdenum disulfide (MoS2 ) mono‐, bi‐, and multilayer films prepared by flake exfoliation and atomic layer deposition (ALD). These films are transferred to different photovoltaic relevant carrier‐selective contacts, such as titanium oxide, titanium–titanium oxide, molybdenum oxide, and silicon–silicon dioxide reference substrates. Raman and photoluminescence (PL) spectra of single‐crystalline exfoliated MoS2 flakes and ALD‐grown MoS2 films on different substrates are compared in order to investigate the influence of the different contact materials on the corresponding optical transitions in MoS2 . It is demonstrated that the different substrates influence the Raman and PL spectra of MoS2 layers due to doping and charge transfer effects, and similar effects are observed in both the exfoliated single‐crystalline flakes and ALD‐grown MoS2 layers. Abstract : This work explores the optoelectronic response of molybdenum disulfide (MoS2 ) in proximity to titanium oxide and molybdenum oxide. The excitonic landscape of MoS2 is observed via photoluminescence spectroscopy. It is found that these contacts induce charge transfer out of the MoS2, additional metal layers influence their behavior, and atomic layer deposition grown MoS2 films behave similarly to exfoliated MoS2 flakes.